Self-Efficacy As a Target for Neuroscience Research on Moderators of Treatment Outcomes in Pediatric Anxiety - Lewis, Krystal M. (J Child Adolesc Psychopharmacol, 2020)
Objective: Despite the advances in the field of neuroscience, many questions remain regarding the mechanisms of anxiety, as well as moderators of treatment outcome. Long-term adverse outcomes for anxious youth may relate to pathophysiologically based information processing patterns and self-referential beliefs, such as self-efficacy. In fact, there are no studies highlighting the relationship between self-efficacy and neurocircuitry in youth. The purpose of this study was to explore the relationships between self-efficacy, brain morphometry, and youth anxiety. Methods: Parent, child, and clinician ratings of anxiety symptoms and child-reported self-efficacy were analyzed in a sample of 8- to 17-year-old youth (n = 51). Measures were collected from all youth at baseline and during and after treatment for the patients. Anxious patients (n = 26) received 12 sessions of cognitive behavioral therapy (CBT). Moreover, imaging data obtained from all participants before treatment were utilized in analyses. Results: Patients reported lower self-efficacy than healthy volunteers. Across the entire sample, anxiety was negatively related to total, social, and emotional efficacy. Both social and emotional efficacy predicted anxiety posttreatment. In addition, social efficacy predicted social anxiety symptoms posttreatment and social efficacy increased across treatment. There were no significant relations between self-efficacy and neurocircuitry. Conclusions: Self-efficacy is an important treatment target for anxious youth. Although self-efficacy was not related to brain morphometry, self-efficacy beliefs may constitute an important mechanism through which CBT and psychopharmacological interventions decrease fear and anxiety symptoms in youth.